The Role of Tax Sanctions and Income Levels on Motor Vehicle Tax Arrears in Banyuwangi Regency - Muhammad Rijalus Sholihin; Lia Rachmawati (STIE Amkop Makassar, 2026)
This study aims to examine the effect of tax sanctions and income levels on motor vehicle tax arrears in Banyuwangi Regency. The research employs a quantitative approach by utilizing both primary and secondary data sources. Primary data were collected through structured questionnaires distributed to motor vehicle taxpayers, while secondary data were obtained from the Technical Implementation Unit of the Banyuwangi Regional Revenue Agency. The research population consisted of registered motor vehicle taxpayers, and a sample of 100 respondents was determined using the Slovin formula to ensure representative data. Data analysis was performed using multiple linear regression to identify the individual and simultaneous effects of the independent variables on motor vehicle tax arrears. The findings reveal that tax sanctions have a significant partial effect on motor vehicle tax arrears, indicating that stricter enforcement and penalties encourage taxpayers to fulfill their obligations promptly. In contrast, income levels do not have a significant partial effect on tax arrears, suggesting that taxpayer compliance is influenced more by regulatory factors than by economic capacity. Furthermore, tax sanctions and income levels jointly have a significant simultaneous effect on motor vehicle tax arrears, demonstrating their combined contribution to explaining taxpayer compliance behavior in Banyuwangi Regency.